Repeated disordered structure for radiative cooling application via scalable stamping method from designed CaCO3 templates - Taweesak Kaewmanee; Patawee Sakata; Pharit Gridtayawong; Worawut Rueangsawang; Chattrarat Ponghiransmith; Nattaporn Chattham; Wisanu Pecharapa; Tanisara Noinonmueng; Wachara Benchaphanthawee; J. Kaewkhao; Supakij Suttiruengwong; Pongsakorn Kanjanaboos (Applied Thermal Engineering, 2026)
Radiative cooling via micro-patterned surfaces provides energy-efficient solution for thermal regulation by enhancing selective thermal emission within the atmospheric transparency window (8–13 μm). This study investigates the effects of microstructural patterning through a low-cost and scalable stamping technique. The patterning templates were uniquely produced by the removal of randomly-distributed CaCO 3 polymorphs—calcite and vaterite with specific sizes. The novel calcite-imprinted structures exhibit superior mid-infrared emissivity (>0.96) and maintain consistent temperature reduction across varying weather conditions, outperforming vaterite-based films. However, the cooling performance of unmodified patterns is limited by solar absorption. To address this, TiO 2 (rutile phase) is incorporated into a polymer matrix before being stamped to enhance solar reflectivity. Moreover, hydrophobic aerogels could be inserted between micropattern gaps to facilitate self-cleaning functionality. A composite film containing 3 wt% TiO 2 with the calcite micro-patterning and hydrophobic aerogel achieves a temperature drop of 4.8 °C, compared to 1.3 °C of pristine patterns relative to that of a clear film. For real-world applicability, the optimized patterning strategies were further validated on fiber cement rooftile surfaces, yielding best temperature reductions of 2.5 °C compared to pattern-free coating under a tropical climate. The calculated net cooling power of 3%wt TiO 2 patterned film with aerogel is 26.9 W/m 2 . This novel passive-cooling stamping strategy is low-cost, scalable, and suitable for large-area deployment, reducing the energy burden of active cooling technologies. • Radiative cooling patterning can be achieved by the removal of CaCO 3 particles. • CaCO 3 is tunable in size and shape as a building block for specific design. • Patterning provides emissivity enhancement within the atmospheric window. • Simple TiO 2 doping results in more reflectivity and cooling efficiency. • The optimized coating provides impactful temperature reduction for roof tile.
Keywords: Calcium Carbonate Crystallization and Inhibition; Radiative Heat Transfer Studies; Thermoelastic and Magnetoelastic Phenomena